Photoluminescence processes in τ-phase Ba1.3Ca0.7-x-ySiO4:xDy3+/yTb3+ phosphors for solid-state lighting. Issue 6 (15th June 2022) - Golja, Desta R.; Woldemariam, Menberu M.; Dejene, Francis B.; Kim, Jung Yong
Abstract : The τ -phase Ba1.3 Ca0.7- x - y SiO4 : x D y 3+ / y Tb 3+ phosphors co-doped with D y 3+ ( x = 0.03) and Tb 3+ ( y = 0.01–0.05) trivalent rare-earth ions were prepared by the gel-combustion method. The structure–property relation of the samples was examined by X-ray diffraction, scanning electron microscopy and spectrophotometer. Here, the effect of Tb 3+ 's concentration on the spectroscopic properties of Ba1.3 Ca0.7- x - y SiO4 : x D y 3+ / y Tb 3+ phosphors was explored by using the photoluminescence excitation, emission and decay curves. Importantly, the photonic energy transfer from (D y 3+ : 4 F9/2 + Tb 3+ : 7 F6 ) to (D y 3+ : 6 H15/2 + Tb 3+ : 5 D4 ) was observed, in which the D y 3+ ions act as a light-emitting donor whereas the Tb 3+ ions as a light-absorbing acceptor, resulting in an enhanced emission from the co-doped Ba1.3 Ca0.7- x - y SiO4 : x D y 3+ / y Tb 3+ ( x = 0.03 and y = 0.01–0.05) phosphors. Finally, the chromaticity coordinates were determined from the measured emission spectra, locating at the green and white light regions. This observation indicates that the characteristic emission colour could be tuned from white to green by varying Tb 3+ concentrations under ultraviolet light.